Microwave structures for generating stable arrays of microplasmas. - Wu, Chen. (2017)
Abstract: Various microwave circuit structures are investigated and shown to support extended arrays of cold microplasmas. Non-thermal or cold microplasma has been intensively investigated because the gas temperature remains low, even at atmospheric pressure. This suggests that atmospheric pressure plasmas may replace arcs and plasma torches in temperature-sensitive applications including treatment of polymers and biomaterials. This thesis builds on the concept that quarter-wave resonators, in the form of microstrip transmission lines, can sustain cold microplasmas. While small linear arrays of such resonators were previously shown to sustain up to 24 microplasmas, the intrinsically weak coupling between resonators was found to be insufficient for longer, more uniform arrays. An electrical connection between each resonator (called a coupling strip) is shown to enhance the coupling among resonators, allowing arrays composed of at least 72 elements that extend 90 mm in length. In addition to linear microplasma arrays, circular-shaped microplasmas have also been demonstrated. Theoretical development of an electromagnetic coupling model known as coupled mode theory shows good agreement with experimental measurements of microplasma emission intensity as well as electromagnetic simulations of these devices. Prospects for scaling the microplasma array to greater lengths are described. These findings may allow for future low-cost plasma processing using roll-to-roll techniques at pressures of one atmosphere.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Electrical Engineering.; Advisor: Jeffrey Hopwood.; Committee: Alan Hoskinson, and Matthew Panzer.; Keywords: Plasma Physics, and .